Use of the ComPact UniLock System for ventral stabilization procedures of the cervical spine - Voss, K.; Steffen, F.; Montavon, P. M. (Veterinary and Comparative Orthopaedics and Traumatology, 2006)
This study evaluates clinical application of the ComPact UniLock™ systema for ventral stabilization of the cervical spine. Patient material included 13 consecutive cases, 12 dogs and one cat, with cervical spinal instabilities secondary to disc-associated wobbler syndrome (six dogs), traumatic, iatrogenic, and disc-associated cervical spinal instability of small dogs (four cases), cervical spinal fractures (one dog and one cat), and congenital atlantoaxial instability (one dog). The 2.0 system was used in smaller patients and the 2.4 system was applied in large dogs. Implant failure was observed on follow-up radiographs in one dog with a healed C2 fracture and screw pullout occurred in one dog with caudal cervical spondylomyelopathy, necessitating revision surgery. Implants remained stable throughout the follow-up period in the other cases. ‘Good’ or ‘ excellent’ clinical outcome was achieved in 12 patients, including the dog with revision surgery. One dog had to be euthanatized due to postoperative deterioration of neurological status and development of pneumonia. The ComPact UniLock system was found to be a suitable implant for treating cervical instabilities of different origin in both small and large patients with lesions from C1/C2 to C6/C7. Some problems were encountered in the dogs with disc-associated Wobbler syndrome, such as lack or slow rate of vertebral fusion and partial collapse of the distracted intervertebral space on follow-up radiographs. A lack of adequate fusion was most likely related to grafting techniques used.
Keywords: Unilock; cervical spine